2023
DOI: 10.1177/03635465231154601
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial of Biologic Augmentation With Bone Marrow Aspirate Concentrate in Patients Undergoing Arthroscopic Rotator Cuff Repair

Abstract: Background: Although initial studies have demonstrated that concentrated bone marrow aspirate (cBMA) injections promote rotator cuff repair (RCR) healing, there are no randomized prospective studies investigating clinical efficacy. Hypothesis/Purpose: To compare outcomes after arthroscopic RCR (aRCR) with and without cBMA augmentation. It was hypothesized that cBMA augmentation would result in statistically significant improvements in clinical outcomes and rotator cuff structural integrity. Study Design: Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“… 12 In the shoulder, randomized trial data exist suggesting those having rotator cuff repairs augmented with BMAC have lower retear rates on magnetic resonance imaging at 1-year postoperatively. 13 For the hip, those with symptomatic labral tears with early degenerative radiographic changes may perform similarly to those without arthritis, if they have intra-articular injection of iliac-crest derived BMAC. 14 Furthermore, those with full-thickness acetabular chondral flaps have better outcome scores after treatment with BMAC as opposed to microfracture.…”
Section: Discussionmentioning
confidence: 99%
“… 12 In the shoulder, randomized trial data exist suggesting those having rotator cuff repairs augmented with BMAC have lower retear rates on magnetic resonance imaging at 1-year postoperatively. 13 For the hip, those with symptomatic labral tears with early degenerative radiographic changes may perform similarly to those without arthritis, if they have intra-articular injection of iliac-crest derived BMAC. 14 Furthermore, those with full-thickness acetabular chondral flaps have better outcome scores after treatment with BMAC as opposed to microfracture.…”
Section: Discussionmentioning
confidence: 99%
“…24 The mean number of MSCs administered was 51,000 ± 25,000 and the patients with fewer MSCs administered had lower rates of intact repairs at long-term follow-up. 24 More recently, Cole et al 25 performed a single-blinded RCT of 91 patients undergoing arthroscopic RCR with and without BMAC augmentation and found higher rates of failed healing in the control group compared with the BMAC group on MRI at 1 year postoperatively (57% vs 18%, P < 0.001). Although these studies demonstrate promising results, there is still an absence of thorough characterization of CTPs in the clinical literature, and more research is needed to correlate the clinical outcome measures with the composition and biological activity of the cells administered.…”
Section: Cell-based Strategiesmentioning
confidence: 99%
“…Overall, our review found 18 case reports/series, RCTs, and case control series examining the effects of MSCs of rotator cuff tears (see Table 1 ) [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. The most notable features of each study are summarized in Table 1 .…”
Section: Mscs For Rotator Cuff Injurymentioning
confidence: 99%